Play where you are - Mita Williams (University of Huddersfield Press, 2022)
This article argues for the position that libraries should develop, host, and encourage the community-creation of location-based games. While Pokémon Go has demonstrated that there is a sizable population ready to go outside to play, it also has left the impression that outdoor games require expensive mobile app-development. But very simple location-specific games can be designed by libraries that can help their community directly experience local sources of underappreciated spaces of natural beauty, help them discover overlooked historical places and their stories, and encourage them to stumble upon local art embedded in the landscape. Rather than only provide online escape rooms for those who may already feel confined by pandemic-related public health restrictions, libraries can create positive mental-health interventions that can also create the potential for a deeper connection between its readers and with where they live through site-specific games. This paper will provide examples of web-based and analog location-based games including a prototype developed by the author.